Xiro3 encodes a Xenopus homolog of the Drosophila Iroquois genes and functions in neural specification. - Bellefroid, E.J.; Kobbe, A.; Gruss, P.; Pieler, T.; Gurdon, J.B.; Papalopulu, N. (The EMBO Journal, 1998)
We have identified in Xenopus and in the mouse two highly related genes, Xiro3 and Irx3 respectively, that encode a Drosophila Iroquois-related homeobox transcription factor. Xiro3 in Xenopus and Irx3 in the mouse are expressed early in the prospective neural plate in a subset of neural precursor cells. In Xenopus, injection of Xiro3 mRNA expands the neural tube and induces ectopic neural tissue in the epidermis, based on the ectopic expression of early neural markers such as Xsox3. In contrast, the differentiation of the early forming primary neurons, as revealed by the expression of the neuronal marker N-tubulin, is prevented by Xiro3 expression. Activation of Xiro3 expression itself requires the combination of a neural inducing (noggin) and a posteriorizing signal (basic fibroblast growth factor). These results suggest that Xiro3 activation constitutes one of the earliest steps in the development of the neural plate and that it functions in the specification of a neural precursor state.